Evaluation of reference evapotranspiration by Penman-Monteith using minimum climatic data in the backcountry of Ceará = Avaliação da evapotranspiração de referência por Penman-Monteith usando dados climáticos mínimos no sertão do Ceará - Mairton Gomes da Silva (Agro@mbiente On-line, 2013)
In areas of semiarid climate, water resources are limited and seriously threatened by excessive exploitation. This study’s objective is to evaluate the performance of the method FAO 56 Penman-Monteith (PM-FAO 56) to estimate the reference evapotranspiration (ETo ) with minimum data (maximum and minimum air temperature) in the backcountry of the state of Ceará. The work was developed based on maximum and minimum air temperatures, relative air humidity, wind speed, and insolation of the conventional stations of the backcountry of Ceará, obtained from the National Institute of Meteorology (INMET). To compare the values of ETo estimated by FAO PM-56 with complete data where the minimum was considered the ratio between the mean (ξ), the standard error of estimation (SEE), correlation coefficient (r), accuracy or concordance index (d) and performance or confidence index (c). Maps of ETo by PM-FAO 56 were made with minimum data for the mesoregion of the backcountry of Ceara, by means of the inverse distance weighted (IDW). The following of estimates of ETo by PM-FAO 56 with maximum and minimum air temperatures worked satisfactorily and by means of spatialisation and generation of thematic maps, it was possible to visualize the ETo in the most remote areas of the region of the study. = Nas regiões de clima semiárido os recursos hídricos são limitados e seriamente ameaçados pela excessiva exploração. Objetivou-se com este estudo avaliar o desempenho do método Penman-Monteith FAO 56 (PM-FAO 56) para estimar a evapotranspiração de referência (ETo) com dados mínimos (temperatura máxima e mínima do ar), no sertão do estado do Ceará. O trabalho foi desenvolvido a partir de dados de temperatura máxima e mínima do ar, umidade relativa do ar, velocidade do vento e insolação das estações convencionais da região do sertão cearense, obtidos com o Instituto Nacional de Meteorologia (INMET). Para comparar os valores de ETo estimados por PM-FAO 56 com dados completos e mínimos foram considerados a razão entre as médias (ξ), o erro padrão de estimativa (EPE), coeficiente de correlação (r), índice de exatidão ou concordância (d) e índice de confiança ou desempenho (c). Foram confeccionados mapas de ETo por PM-FAO 56 com dados mínimos para a mesorregião do sertão do Ceará, por meio do interpolador linear IDW (Ponderação do Inverso da Distância). O procedimento de estimativas de ETo por PM-FAO 56 com dados de temperatura máxima e mínima do ar funcionou satisfatoriamente e por meio da espacialização e geração de mapas temáticos, foi possível visualizar a ETo nas mais remotas áreas da região de estudo.